Analisis Penerapan Sustainability Business Berdasarkan Triple Bottom Line pada Cempedak Private Island - Ummu Nur Syahidah, Nadzifa; Khodijah; Sukmawati, Rati; Rahayu, Pratiwi; Ayu Ningrum, Sekar (Bahtera Inovasi, 2026)
This study aims to analyze the implementation of sustainable business practices at Cempedak Island and their contribution to the company's competitive advantage. The research employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman data analysis technique. The findings indicate that Cempedak Island implements sustainable business practices through the 4C approach, consisting of Conservation, Community, Commerce, and Culture. From an economic perspective, the company empowers local employees, enhances staff competencies, and strengthens customer loyalty. Socially, it carries out educational programs, community empowerment initiatives, and local cultural preservation. Environmentally, the company adopts a zero-waste concept, Black Soldier Fly (BSF)-based waste management, recycling programs, and terrestrial and marine ecosystem conservation. The study concludes that these practices are aligned with the Triple Bottom Line concept, balancing profit, people, and planet. Beyond generating economic, social, and environmental benefits, the implementation of sustainable business practices also contributes to the company's competitive advantage by strengthening its eco-resort image, increasing customer loyalty, improving operational efficiency, and creating service differentiation